Malaria - Dziedzic, Nancy G. (Perspectives on diseases and disorders, 2010)
From the Publisher's Website: Each volume in this timely series provides essential information on a disease or disorder (including symptoms, causes, treatments and cures); presents the controversies surrounding causes, alternative treatments, and other issues; and offers first-person narratives from people coping with the disease-either as patients, family members or caregivers. Essays are carefully edited and introduced to make them easily accessible to student researchers as well as general readers. By focusing on the controversies surrounding diseases and disorders, this series supports debate assignments and helps develop critical thinking skills, and also helps patients and family members learn about and deal with a disease or disorder. Each volume includes numerous color photos, charts, graphs and tables as well as a glossary of key terms, a chronology of developments relating to the disease or disorder, a bibliography to assist with further research, a list of organizations to contact and an index.